ANALYSIS OF THE DEVELOPMENT OF INDONESIAN PALM OIL (CPO) EXPORT BEFORE AND AFTER TRADERS OF THE UNITED STATES OF AMERICA-CHINA - Sri Endang Rahayu; Hastina Febriaty (CERED Indonesia Institute, 2020)
The United States-China trade war has an impact on the current account balance and trade balance. The US-China trade war also caused a decline in the price of CPO, which resulted in a decrease in the number of palm oil exports. The existence of Indonesia's RED policy has experienced a decline in CPO exports to European Union countries. The purpose of this research is to analyze the development of production, volume and export value of Indonesian CPO and to find out which countries are the largest export destinations for Indonesian CPO. This study uses a descriptive approach, which analyzes the development of Indonesian Palm Oil (CPO) exports before and after the United States-China trade war. The data source comes from BPS (Central Bureau of Statistics) in the form of secondary data from 2013-2019. Judging from the area of Indonesian palm oil has an increasing trend from 2013-2019 except in 2016 which decreased by 0.06 million hectares compared to 2015. CPO production every year from 2013 to 2019 has increased. The volume of palm oil exports from 2013 to 2019 experienced increased fluctuation except in 2016 where the export volume decreased by -14%. The countries that are the biggest export destinations for Indonesian CPO are India, China, the Netherlands, Pakistan, Italy, Singapore, Bangladesh, Egypt, Spain, and the United States. The volume of palm oil exports from 2013 to 2019 experienced increased fluctuation except in 2016 where the export volume decreased by -14%. The countries that are the biggest export destinations for Indonesian CPO are India, China, the Netherlands, Pakistan, Italy, Singapore, Bangladesh, Egypt, Spain, and the United States. The volume of palm oil exports from 2013 to 2019 experienced increased fluctuation except in 2016 where the export volume decreased by -14%. The countries that are the biggest export destinations for Indonesian CPO are India, China, the Netherlands, Pakistan, Italy, Singapore, Bangladesh, Egypt, Spain, and the United States.